Effect of adipocytes on the function and activity of T cells in tumor microenvironment - Zhu, Lujia; Xu, Shujun; Ye, Yuhao; Xiong, Yang; Li, Qiushuang (Frontiers in Immunology, 2025)
The tumor microenvironment (TME) comprises non-cancerous cells, extracellular matrix, and signaling molecules that interact with tumor cells. These dynamic interactions critically influence tumor development, progression, metastasis, and treatment response. Cancer-associated adipocytes (CAAs), as a main component of the tumor-adipose microenvironment (TAME), have various functions, including remodeling the extracellular matrix and interacting with tumor cells or infiltrated leukocytes through a variety of mutual signals. Dysfunctional adipocytes can release different metabolic substrates, adipokines and cytokines to affect the activity and function of immune cells in TME, especially T cells, thus promoting the proliferation, progression, invasion and migration of cancer cells. In this review, we summarize the effects of secretions of adipocytes on the activity and function of different types of T cells in TME, and discuss the possible targets of adipocytes in cancer therapy to provide new ideas for anti-cancer therapy by targeting adipocytes.